Identification of multi-color emission from coaxial GaInN/GaN multiple-quantum-shell nanowire LEDs. Issue 1 (9th November 2021) - Ito, Kazuma; Lu, Weifang; Katsuro, Sae; Okuda, Renji; Nakayama, Nanami; Sone, Naoki; Mizutani, Koichi; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu
Abstract : Multi-color emission from coaxial GaInN/GaN MQS nanowire-based light-emitting diodes was identified. A modified epitaxial growth sequence with improved crystalline quality for MQSs was applied to effectively narrow the EL emission peaks. Abstract : Multi-color emission from coaxial GaInN/GaN multiple-quantum-shell (MQS) nanowire-based light-emitting diodes (LEDs) was identified. In this study, MQS nanowire samples for LED processes were selectively grown on patterned commercial GaN/sapphire substrates using metal–organic chemical vapor deposition. Three electroluminescence (EL) emission peaks (440, 540, and 630 nm) were observed, which were primarily attributed to the nonpolar m -planes, semipolar r -planes, and the polar c -plane tips of nanowire arrays. A modified epitaxial growth sequence with improved crystalline quality for MQSs was used to effectively narrow the EL emission peaks. Specifically, nanowire-based LEDs manifested a clear redshift from 430 nm to 520 nm upon insertion of AlGaN spacers after the growth of each GaInN quantum well. This demonstrates the feasibility of lengthening the EL emission wavelength since an AlGaN spacer can suppress In decomposition of the GaInN quantum wells during ramping up the growth temperature for GaN barriers. EL spectra showed stable emission peaks as a function of the injection current, verifying the critical feature of the non-polarization of GaN/GaInN MQSs on nanowires. In addition, by comparing EL and photoluminescence spectra, the yellow-red emission linked to the In-fluctuation and point defects in the c -plane MQS was verified by varying the activation annealing time and lowering the growth temperature of the GaInN quantum wells. Therefore, optimization of MQS nanowire growth with a high quality of c -planes is considered critical for improving the luminous efficiency of nanowire-based micro-LEDs/white LEDs.